Investigation of anilox roller cell clogging - Savickas, Arnas; Stonkus, Rimantas; Jurkonis, Eugenijus (Journal of Graphic Engineering and Design, 2020)
One vital component in the flexo inking system of high-line screen engraving technologies is anilox rollers. These deliver a precise and consistent amount of ink during the process of flexography, making it possible to produce high-resolution prints of exceptional quality. However, as print quality continues to improve, printing houses are experiencing more frequent problems with anilox rollers, such that ink transfer during printing operations is being unpredictably reduced. Due to the lack of research into anilox rollers there is insufficient objective information on how to maintain them at peak performance and condition. This study investigates the clogging of anilox roller cells (without assessing cell wear) in a number of printing houses in the Baltic States. Cell clogging of anilox rollers was determined depending on cell size, ink type and washing method.